Evaluation of neurosensory disturbance after immediate repair of the inferior alveolar nerve transected during sagittal split ramus osteotomy. Issue 5 (September 2021) - Kasahara, Kiyohiro; Sugahara, Keisuke; Nishiyama, Akihiro; Koyachi, Masahide; Koyama, Yu; Koyama, Takumi; Okazaki, Hiroya; Katakura, Akira
Abstract: Bilateral Sagittal split ramus osteotomy (BSSRO) represents the majority of mandibular osteotomies. Intraoperative risks associated with BSSRO include unfavorable fractures, major bleeding episodes, and inferior alveolar nerve (IAN) and lingual nerve damage. In particular, injury to the IAN during BSSRO is a well-documented complication. However, reports of immediate microneural repair of transected IAN are scarce. In this report, we describe a case of neurosensory disturbance due to transection of the IAN during BSSRO. A 20-year-old woman underwent BSSRO at our hospital. Intraoperatively, the IAN was transected during osteotomy, and immediate microneural repair of the IAN was performed combined with polyglycolic acid (PGA) sheet. We performed the stellate ganglion block (27 times), and prescribed 6.6 mg of dexamethasone sodium phosphate postoperatively from the day of the surgery for 14 days and Vitamin B12 for 6 months postoperatively. We evaluated the response to touch sensation using the Semmes-Weinstein monofilaments test (SW test) and two-point discrimination (2PD), pain sensation, and temperature sensation. The right mental nerve did not respond to any quantitative test and sensation of pain just after the operation. One year and three months postoperatively, the SW value was 2.83 and 2PD distance was 11 mm, which were similar to the values on the normal side. The patient responded to sensations of heat and cold and 2-g pain sensation similar to that before the surgery. All responses to sensations were restored to normal one year and three months postoperatively. The postsurgical evaluation revealed marked improvement and significant recovery in sensations of the IAN, following immediate neurorrhaphy combined with PGA sheet during SSRO.